A META-ANALYSIS REPORTING EFFECTS OF ANGIOTENSIN-CONVERTING ENZYME INHIBITORS AND ANGIOTENSIN RECEPTOR BLOCKERS IN PATIENTSWITHOUT HEART FAILURE - G. Savarese; P. Costanzo; J.G.F. Cleland; E. Vassallo; D. Ruggiero; G. Rosano; P. Perrone-Filardi (Столичная издательская компания, 2015)
Translation articles: G. Savarese, P. Costanzo, J.G.F. Cleland, E. Vassallo, D. Ruggiero, G. Rosano, P. Perrone-Filardi «A Meta-Analysis Reporting Effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Patients Without Heart Failure» J Am Coll Cardiol 2013;61(2):131-42;   http://dx.doi.org/10.1016/j.jacc.2012.10.011